Interconnectivity Between Volume Transports Through Arctic Straits. Issue 12 (4th December 2018) - de Boer, Agatha M.; Gavilan Pascual‐Ahuir, Estanislao; Stevens, David P.; Chafik, Léon; Hutchinson, David K.; Zhang, Qiong; Sime, Louise C.; Willmott, Andrew J.
Abstract: Arctic heat and freshwater budgets are highly sensitive to volume transports through the Arctic‐Subarctic straits. Here we study the interconnectivity of volume transports through Arctic straits in three models; two coupled global climate models, one with a third‐degree horizontal ocean resolution (High Resolution Global Environmental Model version 1.1 [HiGEM1.1]) and one with a twelfth‐degree horizontal ocean resolution (Hadley Centre Global Environment Model 3 [HadGEM3]), and one ocean‐only model with an idealized polar basin (tenth‐degree horizontal resolution). The two global climate models indicate that there is a strong anticorrelation between the Bering Strait throughflow and the transport through the Nordic Seas, a second strong anticorrelation between the transport through the Canadian Arctic Archipelago and the Nordic Seas transport, and a third strong anticorrelation is found between the Fram Strait and the Barents Sea throughflows. We find that part of the strait correlations is due to the strait transports being coincidentally driven by large‐scale atmospheric forcing patterns. However, there is also a role for fast wave adjustments of some straits flows to perturbations in other straits since atmospheric forcing of individual strait flows alone cannot lead to near mass balance fortuitously every year. Idealized experiments with an ocean model (Nucleus for European Modelling of the Ocean version 3.6) that investigate such causal strait relations suggest that perturbations in the Bering Strait are compensated preferentially in the Fram Strait due to the narrowness of the western Arctic shelf and the deeper depth of the Fram Strait. Plain Language Summary: The Arctic is one of the most fragile places on the Earth, facing double the rate of warming as the rest of the globe. This warming is partly due to melting of sea ice because open water reflects less sunlight than ice. One of the major controls on Arctic sea ice concentration is the heat flowing into the Arctic through its straits. However, due to the harsh conditions in the Arctic, there are limited long‐term observations of the currents flowing through these straits. Here we turn to climate models to investigate these Arctic straits flows and in particular focus on how flows into and out of the Arctic balance each other. We find that in some instances specific pairs of strait flows are simultaneously affected by large‐scale atmospheric. In other instances, the inflow through one strait flows out through another distant strait because of the way the ocean floor guides the currents. Traditionally, the flows through Arctic straits are studied in relation to local forces such as wind and sea level. Our work suggests value in a more holistic approach; one that also accounts for flow changes in a strait as a response to flow changes in other straits. Key Points: Interannual volume transport variability in Arctic straits must be interconnected to maintain Arctic Ocean mass balance Transports through both the Bering Strait and Canadian Archipelago are correlated to Nordic Seas transport and not to each other Bering Strait transport perturbations are preferentially adjusted in the Nordic Seas due to shelf and strait geometry